Impact of water deficit on the anatomical structure of more productive and less productive cashew trees (Anacardium occidentale L.) in Côte d’Ivoire - Abdoul Rahim Falk Ky; Mory Latif Konaté; N'Guessan François Kouamé (Acta Biologica Slovenica)
This study aimed to understand the mechanism of resilience of the anatomical tissues of organs of the cashew tree in water deficit in the different climatic zones of Côte d'Ivoire. To achieve this, samples of leaves and roots were taken from 55 cashew trees considered high producers (APHP) and 164 neighboring less productive trees (non-APHP) during the dry and rainy seasons. The technique of double staining with green-carmino made it possible to obtain anatomical sections of transversely cut samples under an optical microscope. The thicknesses and surface areas of the sections were measured using Image J software. The thickness of the leaves parenchymas of APHP trees did not show any variation according to the season while the stomatal density increased during the dry season. The thickness of the leaves cortical and medullary parenchymas of non-APHP trees did not show any variation according to the season too but the non-APHPs’ palisade parenchyma thickness increased while their lacunar parenchyma thickness decreased from 37 ± 1.5 mm to 36 ± 3.6 mm during the dry season. The thickness of leaves’ both sides epidermis increased while the thickness of xylem bundles decreased during the dry season to both APHP and non-APHP trees. The number of the roots’ xylem vessels of APHP trees increased from 11 to 27 vessels/mm2 while those of non-APHP trees increased from 15 to 41 vessels/mm2 during the rainy season. The surface area of the midrib medullary parenchyma of APHP trees increased from 4300 ± 837 mm2 to 5800 ± 412 mm2 while those of non-APHP trees increased from 3400  ± 809 mm2 to 5200 ± 993 mm2 during the dry season. The thicknesses of the tissues of APHPs remained greater than those of non-APHPs, regardless of the sampling season.